Assessing socioeconomic dynamics in Windhoek informal settlements in response to the COVID-19 pandemic in Namibia - C N Jona; N P Petrus; C Togarepi; S Shivolo-Useb; J Muzanima; M N T Shipandeni (Environmental Research Communications)
This study conducted an analysis of household income levels in relation to various sociodemographic factors over three distinct periods: pre-COVID-19, during COVID-19, and post-COVID-19. It investigates several determinants of household income categories, including gender, age, educational attainment, marital status, employment status, ownership of a business, and principal source of income. The Samora Machel and Tobias Hainyeko constituencies were purposively selected, and sample respondents were selected in two stages based on probability. A total of 59 households were surveyed using a structured questionnaire that included both open-ended and closed-ended questions. A methodological approach was employed to ascertain the statistical and conceptual importance of the research. Chi-square tests were employed to ascertain the statistical significance of the findings. Based on the findings, work status was identified as a significant predictor of income levels before the onset of COVID-19. During the COVID-19 pandemic, gender and age were significant factors in determining income levels, especially for individuals between the ages of 36 and 59. Age remained a significant factor in determining income levels during the post-COVID-19 period, with the age bracket of 36–59 years experiencing the greatest impact. Nevertheless, there was a significant reduction in gender disparities in income levels. The study revealed that the marital status, level of education, and ownership of a family business had a consistently low association on income levels small across all stages of the study. The-adaptive capacity and resilience were weakened by the COVID-19 pandemic. As such, policies that aim at improving informal settlements should include safety nets strengthening, enhancing job security and employment opportunities as well as capacitating the households in entrepreneurial skills to build resilience for any future shocks.